Pemberian Tokolitik pada G1P0A0 Hamil 28 Minggu Belum Inpartu dengan KPD dan Oligohidramnion - Alvira Balqis Soraya; Dinda Annisa Fitria; Ratna Dewi Puspita Sari (MAJORITY, 2022)
Premature rupture of membranes is a rupture of the amniotic membrane before delivery. It occurs in 3% of pregnancies and carries a risk of preterm delivery. Each year there are 15 million babies born and more than 1 in 10 babies born prematurely (gestation less than 37 weeks). Obtained patient Mrs. IR, 36 years old, came with complaints of preterm pregnancy accompanied by water-discharge. This complaint was felt since two days before entered the hospital, clear color, odor less and changed sanitary napkins three times a day. The patient appeared to be moderately ill, consciousness compos mentis, blood pressure 118/87 mmHg, pulse 83x/minute, breathing 23x/minute and, temperature 36 ° C. The generalist status of the patient was within normal limits. On obstetric examination, there was a TFU of 3 fingers above the umbilicus (24 cm). The lower part of the mother's fetus was round, bouncy, hard with the impression of the head, not yet in PAP. His (-), fetal heart rate 148x/minute. Inspeculo examination found closed OUE, fluorine -, fluxus: +, amniotic (+) inactive, erosion / laceration / poly (-), red litmus (+) to blue. The patient was diagnosed as 28 weeks pregnant G1P0A0 with promiscuity of single live fetal head presentation and oligohydramnios. To prevent preterm labor in this case, conservative therapy is given in the form of antibiotics (prevent in increase dinfection), corticosteroids (fetal lung maturation), and tocolytics (suppress in uterine contractions). To assess the success of tocolytic therapy, the tocolytic index was used.